Avaliação da pressurização do ar na cabina de um trator agrícola em diferentes velocidades de operação e superfícies de deslocamento - Ferreira, Leandro Silveira (2024)
This study aimed to evaluate the air pressurization in the operating compartment of an agricultural tractor at different operating speeds and travel surfaces, including the development (design-build-test) of a prototype – a data logger, with sensors capable of measuring, storing and monitoring psychrometric parameters, such as: barometric and absolute pressures; dry bulb temperature and relative humidity. In the development of the prototype, the reference model of the Agricultural Machinery Development Process (PDMA) was used, with an experiment to evaluate accuracy and precision with data from a meteorological station. An experiment was conducted to study the pressurization in the operator's compartment of an agricultural machine, under the influence of two operating conditions (factors): (i) the travel surface – paved with asphalt and agricultural soil with vegetation cover; and (ii) operating speed – 12 km.h-1, 10 km.h-1, 8 km.h-1, 6 km.h-1 and 4 km.h-1. The machine used was an MF tractor, model 6711. The experiment was conducted with the cabin operating with the ventilation system providing air conditioning at maximum flow. The results of the study, after adjusting the prototype, demonstrated in variance analysis that the prototype presents measurements of psychrometric parameters of barometric pressure, dry bulb temperature and relative humidity with precision. In the experiment with the tractor, it was found by the interaction between the factors that the pressure differential varies with a function: (i) linear, decreasing with the increase in operating speed on vegetated ground; and (ii) quadratic, increasing with the operating speed on paved track. The pressure differential has a positive linear relationship with internal temperature. It is concluded that the movement of the tractor and the vibration triggered by the interaction between the surface and speed, as well as the internal temperature of the cabin, affect the pressure differential.